RHETORICAL PATTERNS OF DISCUSSION SECTIONS OF REPUTABLE INTERNATIONAL JOURNALS - Kasmaini Kasmaini; Riswanto Riswanto; Zahrida Zahrida; Adesti Anggita Putri (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study aims to investigate the rhetorical patterns in the discussion sections of reputable international journals (Q1) in the field of English language teaching using a qualitative content analysis design. The discussion sections of the selected journals are analyzed using the Ruiying and Allison model (2003). A total of 30 articles served as the research corpus. This study will reveal the rhetorical patterns (based on the Ruiying and Allison model). The findings indicate that certain moves and steps are consistently present across the articles, reflecting conventional or obligatory rhetorical practices. Moves 2 and all steps of Move 4 were observed in 100% of the articles, identifying them as obligatory elements in structuring discussion sections. Other moves, such as Moves 1, 3, 5, 6–Step 1, and 6–Step 2, appeared in 90–96.6% of the articles, demonstrating their conventional but non-obligatory nature. In contrast, optional steps, including Move 6–Step 3 and Move 7–Step 3, were present in only 30–36.7% of the articles, suggesting that they are not essential to the overall rhetorical structure. These results can serve as valuable resources for academic writing courses.